2016
DOI: 10.1007/s13277-016-5410-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential miRNA expression in pleural effusions derived from extracellular vesicles of patients with lung cancer, pulmonary tuberculosis, or pneumonia

Abstract: MicroRNAs (miRNAs) have been found to play important regulatory roles in various physiological and pathological processes. MiRNAs also exhibit high stability and are present at high concentrations in human bodily fluids. Consequently, miRNAs may represent attractive and novel diagnostic biomarkers for certain clinical conditions. Recently, the capacity for extracellular vesicles, including microvesicles and exosomes, to carry miRNAs that participate in cell-to-cell communication has been described. In the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 58 publications
1
44
0
1
Order By: Relevance
“…Furthermore, one study has suggested that a miRNA signature is more accurate in the classification of poorly differentiated tumors than mRNA. 20 Exosomal miRNA signatures of several types of cancer, including non-small cell lung cancer, [21][22][23][24] pancreatic cancer, 25 and hepatocellular carcinoma, 26 have been profiled. However, studies focused on the exosomal miRNAs derived from BC are still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, one study has suggested that a miRNA signature is more accurate in the classification of poorly differentiated tumors than mRNA. 20 Exosomal miRNA signatures of several types of cancer, including non-small cell lung cancer, [21][22][23][24] pancreatic cancer, 25 and hepatocellular carcinoma, 26 have been profiled. However, studies focused on the exosomal miRNAs derived from BC are still limited.…”
Section: Introductionmentioning
confidence: 99%
“…miR‐378a is reported to be implicated in colorectal cancer as a tumor suppressor (43) and also in metabolism and angiogenesis (44). miR‐378i was also found in colorectal cancer samples (45) and in patients with lung cancer, pulmonary tuberculosis, or pneumonia (46). Its role in HMEEC‐secretion exosomes is unclear and understudied.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, tumor and stromal cells can regulate the invasiveness of cancer cells through exosome-mediated delivery of protein and miRNA in the regulation of EMT-related pathways. In lung cancer cells and in late stage of lung cancer serum, an involvment of exosome as drivers of epithelial to mesenchymal transition has been recently reported, furthermore Lin et al, demonstrated that contents exosomes miR-205-5p and miR-200b were markedly increased in malignant pleural effusion [41,42].…”
Section: Exosomementioning
confidence: 94%